Microbial Conversion of Rice Straw Into Lactic Acid Through Simultaneous and Separate Hydrolysis and Fermentation - Yuliana, Eva; Indrati, Retno; Setyabudi, Francis Maria Constance Sigit; Ningsih, Dewi Pujo; Sardjono, Sardjono (agriTECH, 2025)
Lactic acid is often produced from lignocellulosic materials through various steps, including pretreatment, hydrolysis, and fermentation. Therefore, this study aims to evaluate the conversion of lactic acid from rice straw using simultaneous and separate hydrolysis and fermentation. The process was initiated with and without pretreatment using Ca(OH)2 at 85 °C for 16 hours, followed by hydrolysis using Trichoderma reesei PK1J2 and fermentation with Rhizopus oryzae AT3. Hydrolysis and fermentation were performed simultaneously and separately. The results showed that pretreatment could reduce lignin content, but this process was not needed because Trichoderma reesei PK1J2 degraded lignin during hydrolysis. In addition, fermentation conditions in this study could not support the production of lactic acid by Rhizopus oryzae AT3. Based on biomass growth during the treatment, simultaneous hydrolysis and fermentation (108 mg/g dry substrate) was better compared to separate hydrolysis and fermentation (104 mg/g dry substrate).